Global research trends and hotspots in Parkinson’s disease psychosis: a 25-year bibliometric and visual analysis - Wu, Jianhong; Jin, Xin; Xie, Weiming; Liu, Liang; Wang, Fei; Zhu, Ling; Shen, Yuan; Qiu, Linghe (Frontiers in Aging Neuroscience, 2024)
BackgroundParkinson’s disease psychosis (PDP) is one of the most severe and disabling non-motor symptoms in the progression of Parkinson’s disease (PD), significantly impacting the prognosis of PD patients. In recent years, there has been an increase in literature on PDP. However, bibliometrics has rarely been applied to PDP research. This study provides an overview of the current state of PDP research and predicts future trends in this field.MethodsThe literature search was conducted using the Web of Science Core Collection, with the search terms (Parkinson* AND (psychotic* OR hallucination* OR illusion* OR delusion* OR misperception* OR psychosis OR psychoses)). VOSviewer and CiteSpace software were employed to perform bibliometric analysis and visual representation of the search results.ResultsA total of 603 articles were effectively included. Since 2017, there has been a significant upward trend in publications related to PDP. The United States, the United Kingdom, and Canada were the top three contributing countries in terms of publication volume, with France also having a strong influence in this field. Movement Disorders and King’s College London included and published the most articles on PDP. The paper titled “Hallucinations in Parkinson’s Disease: Prevalence, Phenomenology, and Risk Factors” received the highest number of citations and average citations. Cluster analysis results identified brain, prevalence, connectivity, and atypical antipsychotics as key hotspots in this field. High-frequency keywords were grouped into three themes: neurobiology, therapeutic strategies, and symptom research. Among them, pimavanserin, risk, and functional connectivity have been the most studied areas in the past 7 years and are likely to remain key topics in future research.ConclusionResearch on PDP has garnered increasing attention. This study visualizes PDP research over the past 25 years to analyze global hotspots and trends. It offers researchers a valuable perspective for identifying key topics and understanding research trajectories in this expanding field.